PERANCANGAN AUGMENTED REALITY BERBASIS MARKER PADA GEDUNG LABORATORIUM SENTRAL ILMU HAYATI UNIVERSITAS BORNEO TARAKAN - Awang Pradana; edy utomo; dedy harto; arif fadllullah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Social distancing during the Covid-19 pandemic even several regions in Indonesia imposed lockdown levels, so that several jobs and in the education sector were implemented virtually. One technology that relies on the virtual sector is AR, a technology that performs visualization in virtual data or objects are combined with real conditions. This technology allows users to view virtual objects in 3D and can even provide a new experience interact directly with these virtual objects. Therefore, based on this experience, this proposes design of AR with the marker method, the object being worked on is the LSIH at Universitas Borneo Tarakan. The research will use a smartphone to capture images in real-time and the catches will be processed using a marker-based, until a 3D image object is obtained, which can be viewed from various angles. It is hoped that the research that will be designed will produce 3D from the building with the a smartphone which is taken in real-time and can be more effective, fast and accurate with dynamic performance. In other words, this research training was built in order to promote a form of introduction to one of the laboratory buildings located at the UBT to the public, especially those in the city of Tarakan.